The effects of caffeine ingestion on isokinetic muscular strength: A meta-analysis. Issue 3 (March 2019) - Grgic, Jozo; Pickering, Craig
Abstract: Objectives: The aims of this paper are threefold: (1) to summarize the research examining the effects of caffeine on isokinetic strength, (2) pool the effects using a meta-analysis, and (3) to explore if there is a muscle group or a velocity specific response to caffeine ingestion. Design: Meta-analysis. Methods: PubMed/MEDLINE, Scopus, and SPORTDiscus were searched using relevant terms. The PEDro checklist was used for the assessment of study quality. A random-effects meta-analysis of standardized mean differences (SMDs) was done. Results: Ten studies of good and excellent methodological quality were included. The SMD for the effects of caffeine on strength was 0.16 (95% CI = 0.06, 0.26; p = 0.003; +5.3%). The subgroup analysis for knee extensor isokinetic strength showed a significant difference ( p = 0.004) between the caffeine and placebo conditions with SMD value of 0.19 (95% CI = 0.06, 0.32; +6.1%). The subgroup analysis for the effects of caffeine on isokinetic strength of other, smaller muscle groups indicated no significant difference ( p = 0.092) between the caffeine and placebo conditions. The subgroup analysis for knee extensor isokinetic strength at angular velocities of 60° s −1 and 180° s −1 showed a significant difference between the caffeine and placebo conditions; however, no significant effect ( p = 0.193) was found at an angular velocity of 30° s −1 . Conclusions: This meta-analysis demonstrates that acute caffeine ingestion caffeine may significantly increase isokinetic strength. Additionally, this meta-analysis reports that the effects of caffeine on isokinetic muscular strength are predominantly manifested in knee extensor muscles and at greater angular velocities.